Learn intermediate C# scripting for Unity game development (Packt Publishing, 2023)
Welcome to an exciting journey through advanced Unity game development and C# scripting. In the first section of this course, you will embark on a Unity C# scripting crash course, refreshing and solidifying your scripting skills for Unity game development. Moving forward, you will explore the world of C# data structures, including lists, stacks, queues, and dictionaries, and learn how to implement them within Unity projects. As you progress, you will dive into object pooling in Unity with C#, a powerful design pattern that you will seamlessly integrate into your scripts. Practical experience awaits as you apply object pooling in a real Unity 2D game project, enhancing your game development capabilities. Additional exploration of C# scripting concepts, such as namespaces, coroutines, static variables and functions, and function overloading, will further enrich your expertise. By the end of the course, you will not only strengthen your C# scripting skills but also expand your knowledge across diverse areas, from data structures and object pooling to vectors, quaternions, and object-oriented programming in C#. What You Will Learn Learn about stack, queues, and dictionaries and their applications Learn how to create a growing object pool Explore the working of Euler Angles in C# Learn to combine multiple quaternion rotations in C# Learn about static variables, functions, and classes in C# Learn to work with attributes in Unity Audience This intermediate course caters to aspiring game developers with some foundational knowledge of Unity and C# scripting. It's also suitable for programmers and developers eager to elevate their skills in Unity game development. Whether you are keen on delving into advanced techniques, gaining hands-on experience with complex game features, or simply looking to bridge the gap between basic and advanced Unity scripting proficiency, this course is tailored to help you achieve your goals and become a more proficient game developer. About The Author Raja Biswas: Raja Biswas has taught game development and computer programming to thousands of people through his YouTube channel--Charger Games. He has helped many viewers publish their first game through his videos and has encouraged them to learn computer programming as well. He has a passion for learning new things and teaching those to anyone looking to learn. Every day, Raja gets emails from all over the world, thanking him for all that he teaches through his tutorial videos. He is from India and has a diploma in engineering in computer science and technology and a bachelor's degree in engineering in IT. He has learned and developed most of his skills from books and online tutorials and believes that anyone can learn anything today with the power of the Internet.